Clinical Spectrum of Severe Acute Respiratory Syndrome Coronavirus 2 Infection and Protection From Symptomatic Reinfection. (19th August 2021) - Maier, Hannah E; Kuan, Guillermina; Saborio, Saira; Carrillo, Fausto Andres Bustos; Plazaola, Miguel; Barilla, Carlos; Sanchez, Nery; Lopez, Roger; Smith, Matt; Kubale, John; Ojeda, Sergio; Zuniga-Moya, Julio C; et al.
Abstract: Background: There are few data on the full spectrum of disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection across the lifespan from community-based or nonclinical settings. Methods: We followed 2338 people in Managua, Nicaragua, aged <94 years from March 2020 through March 2021. SARS-CoV-2 infection was identified through real-time reverse transcription polymerase chain reaction (RT-PCR) or through enzyme-linked immunosorbent assay. Disease presentation was assessed at the time of infection or retrospectively by survey at the time of blood collection. Results: There was a large epidemic that peaked between March and August 2020. In total, 129 RT-PCR–positive infections were detected, for an overall incidence rate of 5.3 infections per 100 person-years (95% confidence interval [CI], 4.4–6.3). Seroprevalence was 56.7% (95% CI, 53.5%–60.1%) and was consistent from age 11 through adulthood but was lower in children aged ≤10 years. Overall, 31.0% of the infections were symptomatic, with 54.7% mild, 41.6% moderate, and 3.7% severe. There were 2 deaths that were likely due to SARS-CoV-2 infection, yielding an infection fatality rate of 0.2%. Antibody titers exhibited a J-shaped curve with respect to age, with the lowest titers observed among older children and young adults and the highest among older adults. When compared to SARS-CoV-2–seronegative individuals, SARS-CoV-2 seropositivity at the midyear sample was associated with 93.6% protection from symptomatic reinfection (95% CI, 51.1%–99.2%). Conclusions: This population exhibited a very high SARS-CoV-2 seropositivity with lower-than-expected severity, and immunity from natural infection was protective against symptomatic reinfection. Abstract : A community-based cohort in Managua, Nicaragua, had very high severe acute respiratory syndrome coronavirus 2 seropositivity but lower-than-expected severity. Overall, 69% of infections were asymptomatic or subclinical and 1.1% of infections were severe. Seropositivity was associated with 93.6% protection from symptomatic reinfection through March 2021.